The Corrosion Behavior of Sputter-Deposited Nanocrystalline W-Cr Alloys in Nacl and NaohaSolutions - Basnet, Minu; Bhattarai, Jagadeesh (Journal of Nepal Chemical Society, 2010)
The corrosion behavior of the sputter-deposited nanocrystalline W-Cr alloys was studied in 0.5 M NaCl and alkaline 1 M NaOH solutions at 25°C, open to air using immersion tests and electrochemical measurements. Chromium metal acts synergistically with tungsten in enhancing the corrosion resistance of the sputter-deposited W-Cr alloys so as to show higher corrosion resistance than those of alloy-constituting elements in both 0.5 M NaCl and 1 M NaOH solutions. In particular, the nanocrystalline W-Cr alloys containing 25-91 at% chromium showed about one order of magnitude lower corrosion rates (that is, about 1-2 × 10-3 mm.y-1) than those of tungsten and chromium metals even for prolonged immersion in 0.5 M NaCl solution at 25°C. On the other hand, the corrosion rate of the sputter-deposited W-Cr alloys containing 25-75 at % chromium was decreased significantly with increasing chromium content and showed lowest corrosion rates (that is, 1.5-2.0 × 10-3 mm.y-1) after immersed for prolonged immersion in 1 M NaOH solution. The corrosion rates of these nanocrystalline W-(25-75)Cr alloys are nearly two orders of magnitude lower than that of tungsten and more than one order of magnitude lower corrosion rate than that of sputter-deposited chromium metal in 1 M NaOH solution. The corrosion-resistant of all the examined sputter-deposited W-Cr alloys in 0.5 M NaCl solution is higher than in alkaline 1 M NaOH solution at 25°C. Open circuit potentials of all the examined W-Cr alloys are shifted to more noble direction with increasing the chromium content in the alloys after immersion for 72 h in both 0.5 M NaCl and 1 M NaOH solutions at 25°C, open to air. Keywords: Sputter deposition, nanocrystalline W-Cr alloys, corrosion test, electrochemical measurement, NaCl and NaOH solutions. DOI: 10.3126/jncs.v25i0.3300 Journal of Nepal Chemical Society Volume 25, 2010 pp 53-61